Introduction, Analysis, and Review on the Book: "An Introduction to Sufism, the Inner Path of Islam" - Maryam Saneapour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article introduces, analyzes, and criticizes the book entitled: "An Introduction to Sufism, the Inner Path of Islam" written by Eric Geoffroy and translated from French to English by Roger Gaetani. Geoffroy, in this work, explains the inner spirituality of Islam. He has studied Sufism from many aspects and reviewed the origins of the Islamic Mysticism up to present. The author has used Sufism as a magnifier, and he has observed a unique spirituality which is existed in all the inner forms of Islam.One of the advantages of this book is its wide historical perspective which considers the most important Sufi dervishes from the early days of Sufism formation up to now. Moreover, Geoffroy has studied the discussions, theories, and practices which caused to form Sufism fairly and accurately.  In this book, the global and unifying aspects of Sufism which can contrast with radical sectarianisms have been highlighted.  Geoffroy has attempted to make a balance between the early Islamic mystics like special treatment of the subject balances the voices of long ago as Ibn Arabi, Rumi, Hallaj, etc. and the contemporary mystics.In this article, the most important issues of the book have been emphasized, and their positive or negative aspects have been reviewed.